Tuberculosis epidemiology in northeastern Brazil, 2015 – 2019 (Research, Society and Development, 2020)
Objective: to evaluate the epidemiological profile of tuberculosis in the Northeast Region in the last 5 years. Methodology: this is a descriptive, retrospective and quantitative epidemiological study of confirmed cases of tuberculosis in the Northeast of Brazil in the period from 2015 to 2019. Results: In the last 5 years, 117,638 cases of tuberculosis were reported in the Northeast. When analyzing the profile of individuals with tuberculosis, it was found that 68% are male, aged 20 to 39 years old, equivalent to 43% of cases, followed by individuals aged 40 to 59 years old who represent 32%. The most prevalent clinical form of tuberculosis in the period was pulmonary (86%) of the cases. They have AIDS 9,550 (14%), 10,269 (16%) have diabetes, 22,019 (34%) are smokers and 23,237 (6%) use alcohol. Conclusion: Tuberculosis remains a disease today, far from eradication in the Northeast. The epidemiological aspects highlighted by the research reveal the need for planning health services regarding the training of professionals to fight tuberculosis.